PENGARUH IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SD NEGERI I KADIPIRO YOGYAKARTA - Siti Maisaroh (Elementary School: Jurnal Pendidikan dan Pembelajaran ke-SD-an, 2015)
This research is aimed to understand the effect of school based management implementation to the development of educational quality at Local Elementary School I ofKadipiro of Yogyakarta. This research is quantitative research. Free variable in the research isschool based management implementation and the bonded variable is the development ofeducational quality. Population in the research are the elementary school teachers of LocalElementary School I of Kadipiro of Yogyakarta. Whereas the samples are obtained based onrandom sampling technique. Method that used in the data obtaining is questionnaire,documentation, interview, and observation, whereas the data analysis uses simple linearregression. The result of the research shows that school based manajemen implementation arepositioned in the good category shown by average observation value as much as 78,94. Whereasthe development of educational also positioned at the good category with average observationvalue as much as 79,94. WhereasÂ  regression analysis result shows that there is positive effectbetween school based manajement implementation to the development of educational qualityshown by calculated t (3,245) is higher than tÂ values (2,10).tabel